Pengaruh Disiplin Kerja, Kepuasan Kerja Dan Lingkungan Kerja Fisik Terhadap Kinerja Karyawan Pada PT Bhirawa Mitra Sentosa Sidoarjo - Evi Nur Indah Sari; Miftahul Munir; Endah Kurniawati (Politeknik Kampar, 2023)
This study discusses the effect of work discipline, job satisfaction and physical work environment on employee performance at PT Bhirawa Mitra Sentosa Sidoarjo. This study aims to determine and explain the results of the influence of work discipline, job satisfaction and physical work environment on employee performance at PT Bhirawa Mitra Sentosa Sidoarjo. The sample of this research is all employees who are in the office, namely as many as 53 employees. The sampling technique uses non-probability sampling, namely saturated sampling. The analysis technique used is the classical assumption, multiple linear regression. The results of this study are that there is a positive and significant effect of work discipline on employee performance with a significant value of 0.000 < 0.05. There is a positive and significant effect of job satisfaction on employee performance with a significant value of 0.000 < 0.05. There is a positive and significant influence of the physical work environment on employee performance with a significant value of 0.001 < 0.05. There is an effect of work discipline, job satisfaction and physical work environment simultaneously on employee performance with a significant value of 0.000 < 0.05.